2017
DOI: 10.1021/acs.macromol.7b00824
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Segmental Configuration on Properties of n-Propyl-Bridged Polycyanurate Networks

Abstract: The effect of the chemical configuration of network segments on the physical properties, cure properties, mechanical performance, and chemical stability of polycyanurate networks was investigated via synthesis, network formation, and characterization of an isomeric series of npropyl-bridged cyanate ester monomers. Configurations that provide cyanurate oxygen atoms with either nearby methyl groups or nearby bridge groups exhibited decreased moisture uptake by up to 50%, along with a roughly 20−40 °C reduction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…A consistent melting endotherm for monomer 1 was not attainable. Experience in handling this monomer revealed that the supercooled liquid is stable for very long periods, with crystal growth requiring time periods that are impractically long for DSC analysis. Among the remaining isomers 2 – 4 , there is considerable variation in both the enthalpy (range equal to about 50% of the average value) and entropy (range equal to about 40% of average) of melting when measured at the melting point.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A consistent melting endotherm for monomer 1 was not attainable. Experience in handling this monomer revealed that the supercooled liquid is stable for very long periods, with crystal growth requiring time periods that are impractically long for DSC analysis. Among the remaining isomers 2 – 4 , there is considerable variation in both the enthalpy (range equal to about 50% of the average value) and entropy (range equal to about 40% of average) of melting when measured at the melting point.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The four dicyanate ester monomers were prepared and purified according to literature methods. , Solvents were obtained commercially and used as received.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microporous cyanate resins represent a new class of MOPs developed in our group since 2009 that potentially extend the applications of thermosetting cyanate resins to other high-tech fields, e.g., adsorption of gases and organic vapors. Using multifunctional cyanate monomers, upon heating, every three OCN groups are thermally cyclotrimerized to form a triazine ring, which acts as net node in the hyper-cross-linked microporous cyanate resin networks.…”
Section: Introductionmentioning
confidence: 99%
“…This development mainly focuses on improving the thermal properties, dielectric properties, and flame retardancy of the resin. Zhan et al synthesized an isomeric series of n-propyl-bridged cyanate ester monomers [15]. They reported that when cyanurate oxygen atoms were nearby methyl groups or bridge groups, the resin exhibited a decreased moisture uptake by up to 50%, along with an approximately 20-40 °C decrease in the glass transition temperature.…”
Section: Introductionmentioning
confidence: 99%